"We were told that the content we delivered was not as important:" disconnect and disparities in world language student teaching during COVID-19. (December 2021) - Back, Michele; Golembeski, Karli; Gutiérrez, Alexander; Macko, Tyler; Miller, Sean; Pelletier, D.'Lanie
Abstract: Student teaching, the most important stage of a teacher candidate's preparation, was profoundly affected by the COVID-19 pandemic. For world language (WL) student teachers, the effects were even more pronounced, as language learning and teaching were given an even lower priority than usual. In this study we use collaborative, co-constructed autoethnographic narratives to explore how five participant researchers experienced the sudden shift to emergency remote learning during the beginning stages of the pandemic. Findings indicate an overall feeling of disconnect from classroom practices and district communication, followed by disparate student teaching experiences depending upon the districts' socioeconomic makeup. Other findings corroborate previous research demonstrating decreased student engagement and diminished attention to world language as a content area by both districts and families. However, we also believe that our experiences during the pandemic allowed us to acquire important skills in online teaching and caring for students, which we plan to utilize in our future careers. Within the context of these findings, we offer suggestions for future emergency remote teaching situations in the context of WL teacher education.